The penal narratives of community sentence and the role of probation: The case of the Wrocław model of community service - Matczak, Anna (European journal of probation, 2021)
This article draws on Robinson, McNeill and Maruna’s argument about the adaptability of community sanctions and measures, observed through four distinctive penal narratives, in order to shed light on the regional development of community service in Wrocław, Poland. While the managerial adaptation of community sanctions is underpinned by an inter-agency cooperation to fulfil the goals of the system, the contemporary rehabilitation iteration has become a toolkit of measures predominantly phrased around risk management, the reparative discourse seeks various means to repair harm and the punitive orientation represents the turn to desert-based and populist sentencing frameworks. In this article, the first three are reflected upon along with the emerging, restorative adaptation of community sanctions. The last one is added to expand on the findings of this author’s previous research, which suggests the viability of the restorative orientation for community service in Poland. A brief discussion of how punishment, probation and restorative justice can be reconciled is followed by the introduction of Polish probation and the role of probation officers in delivering community service in Poland. Although the penal narratives are visible in the Wrocław model to different degrees and in various combinations, more research is required to evaluate the viability of a progressive orientation to punishment during a gradual optimisation of community orders.